Effects of strain and strain rate on dynamic recrystallization and solid-state welding behaviors of aluminum alloys - Yuelin Wang; Guoqun Zhao; Lu Sun; Xiaowei Wang (Journal of Materials Research and Technology, 2024)
In order to study the effects of strain (ɛ) and strain rate (ε˙) on the dynamic recrystallization (DRX) and solid-state welding behaviors of aluminum alloys, hot compression welding experiments with different strains and strain rates on 6063 aluminum alloys were conducted in this paper. The microstructures of the welding zones and near the welding interfaces were observed and characterized. The results show that continuous dynamic recrystallization (CDRX) is not the only DRX mode during hot deformation process of aluminum alloys. The DRX and interfacial bonding behaviors are influenced by strain rate. The dominant DRX mode is CDRX at a strain rate of 0.1 s−1, while discontinuous dynamic recrystallization (DDRX) dominates when the strain rate increases to 30 s−1. This is because a lower strain rate is conducive to dynamic recovery (DRV) and subgrain rotation, which then excites CDRX, while a higher strain rate is conducive to grain boundary bulging. The interfacial closure under CDRX action is mainly dependent on engulfing and growing of the DRX grains, while that under DDRX action is mainly dependent on interface grain boundaries (IGBs) migration.